Education in occupational health psychology: Where have we been, where are we now and where are we going? - Houdmont, Jonathan; Leka, Stavroula; Cox, Tom (ISMAI Publishers, 2007)
At the first full conference of the European Academy of Occupational Health Psychology (Lund, 1999), the decision was ratified to organise activities around three fora. These together represented the pillars on which the European Academy had been founded that same year: education, research and professional practice. Each forum was convened by a chair person and a small group of full members; it was agreed that a forum meeting would take place at each full conference and working groups would be established to move developments forward between conferences. The forum system has proven an effective means by which to channel the energies of individual members, and the institutions that they represent, towards advancements in all three areas of activity in occupational health psychology (OHP) in Europe. During the meeting of the education forum at the third full European Academy conference (Barcelona, 2001), the proposal was made for the establishment of a working party that would be tasked with the production of a strategy document on The Promotion of Education in Occupational Health Psychology in Europe. The proposal was ratified at the subsequent annual business meeting held during the same conference. The draft outline of the strategy document was published for consultation in the European Academy’s e-newsletter (Vol. 3.1, 2002) and the final document presented to the meeting of the education forum at the fourth full conference (Vienna, 2002). The strategy document constituted a seminal piece of literature in so far as it provided a foundation and structure capable of guiding pan-European developments in education in OHP – developments that would ensure the sustained growth of the discipline and assure it of a long-standing embedded place in both the scholarly and professional domains. To these ends, the strategy document presented six objectives as important for the sustained expansion and the promotion of education in the discipline in Europe. Namely, the development of: [1] A core syllabus for education in occupational health psychology [2] A mechanism for identifying, recognising and listing undergraduate and postgraduate modules and courses (programmes) in occupational health psychology [3] Structures to support the extension of the current provision of education in occupational health psychology [4] Ways of enhancing convergence of the current provision of education in occupational health psychology [5] Ways of encouraging regional cooperation between education providers across the regions of Europe [6] Ways of ensuring consistency with North American developments in education and promoting world wide co-operation in education Five years has elapsed since the presentation of these laudable objectives to the meeting of the education forum in Vienna in December 2002. In that time OHP has undergone considerable growth, particularly in Europe and North America. Expansion has been reflected in the evolution of existing, and emergence of new, representative bodies for the discipline on both sides of the Atlantic Ocean. As such, it might be considered timely to pause to reflect on what has been achieved in respect of each of the objectives set out in the strategy document. The current chapter examines progress on the six objectives and considers what remains to be done. This exercise is entered into not merely in order to congratulate achievements in some areas and lament slow progress in others. Rather, on the one hand it serves to highlight areas where real progress has been made with a view to the presentation of these areas as ripe for further capitalisation. On the other hand it serves to direct the attention of stakeholders (all those with a vested interest in OHP) to those key parts of the jigsaw puzzle that is the development of a self-sustaining pan-European education framework which remain to be satisfactorily addressed.